Walking With Meaning - Jennifer McDuff; Alison Phinney (SAGE Publishing, 2015)
Physical activity is beneficial for people with dementia, but little research explores subjective experiences of physical activity in this population. Interpretive description guided the analysis of 26 interviews conducted with 12 people with dementia. Three themes described the subjective meaning of everyday physical activity: Participants were attracted to activity because it improved physical well-being, provided social connections, gave opportunity to be in nature, and provided structure and focus; participants experienced impediments to activity because of physical discomfort, environmental factors, lack of enthusiasm, and memory loss; and participants made adjustments by choosing walking over other activities and by being active with others. Results show that physical activity remains important for people with dementia, although they encounter barriers. They may prefer walking with others as a form of activity. Findings could influence how nurses conceptualize wandering and suggest that walking programs could be well received by people with dementia.